Content analysis of alternative music from 1990 to 1999 - Gador, Oscar Ledesma, III 1976-
This study is a content analysis of alternative music from 1990 to 1999. The study aims to determine the main themes of alternative songs and how they affect the socio-political views of its listeners in presenting alternative music in language, type of music, instruments and music tone. The model used is Interdependence of Structures according to Isabel Fernandez in her undergraduate thesis "Philippine Pop Music from its Birth to its Development." The communication model has a main foundation - socio-economic reality of society - which was three substructures in the form of political, social and cultural. Alternative music is under the cultural structure, which is affected by the political and social structures and thus reflects society. The study used a content analysis form in determining the characteristics of fifty (50) songs. The variables of the content analysis form are language, type of music, instrument, music tone and theme. The researcher also conducted a one-shot survey with fifty (50) respondents to determine the preference of alternative music listeners and how they were affected by the music. Findings revealed that the main themes of alternative music were social issues (8), simple living (8), environmental concerns (6), nationalism (5), anti-government (4) and romantic love (4). Most of the songs used the Filipino language (22) with the guitar (25) as the main instrument. Folk rock (12) was the top category and most songs had an angry tone (12). Most of the respondents were affected by alternative music (33) on their views on social issues (32), patriotism (27), environment protection (26) and government policies (17). The respondents learned about alternative music from their friends (37) abd from the broadcast media (34). Others heard from live performances and concerts of alternative artists (29). Respondents prefer the use of Filipino (23) in the hard rock (26) and ethnic (26) category with the guitar (30) as the main instrument and having a funny or happy tone (19). The favorite themes are social problems (41) like poverty and unemployment followed by romantic love (34).